Overdenture: An alternative treatment for oral rehabilitation in patients with early childhood caries - Márcia Alves Pereira dos Santos; Liz Helena Moraes Pinheiro; Rafael de Lima Pedro; Lívia Azeredo Alves Antunes; Laura Guimarães Primo (Journal of Dental Problems and Solutions - Peertechz Publications, 2021)
Oral rehabilitation in child is an odontopediatric challenge once the restorative treatament needs to be done in quick procedures and few visits for maintain cooperative child behaviour. With these objectives in mind, the present report describes an oral rehabilitation using fixed prosthesis (overdenture) in a 3-year-old boy who had early childhood caries and whose dental roots had been endodontically treated. The use of this device is a good aesthetic and functional solution for early teeth lost. Thus, this treatment approach allowed a harmonic dental maintenance in relation to other structures of the stomatognathic system, thus supporting the maxillary development and guiding the eruption of the permanent teeth, in addition to increasing patient and family satisfaction.